Intimate partner violence in couples navigating incarceration and reentry. Issue 5 (4th July 2018) - McKay, Tasseli; Landwehr, Justin; Lindquist, Christine; Feinberg, Rose; Comfort, Megan; Cohen, Julia; Bir, Anupa
Abstract: Qualitative and preliminary quantitative research suggests that reentry from prison could be a time of heightened intimate partner violence (IPV) risk. Using data from 666 different-sex couples who participated in the dyadic, longitudinal Multi-site Family Study of Incarceration, Parenting and Partnering, we found that physical violence and controlling behavior were highly prevalent before and after incarceration. Women were more likely than their male partners to experience severe and frequent physical partner violence victimization. Participants with stronger healthy relationship beliefs, stronger conflict resolution skills, and longer relationship duration were less likely to report violence after the male partner's release from prison.